The republic : and, the laws - Cicero, Marcus Tullius; Rudd, Niall; Powell, J. G. F.; Cicero, Marcus Tullius; Cicero, Marcus Tullius (Oxford : Oxford University Press, 1998)
However one defines Man, the same definition applies to us all. This is sufficient proof that there is no essential difference within mankind.' (Laws l.29-30) Cicero's The Republic is an impassioned plea for responsible governement written just before the civil war that ended the Roman Republic in a dialogue following Plato. Drawing on Greek political theory, the work embodies the mature reflections of a Roman ex-consul on the nature of political organization, on justice in society, and on the qualities needed in a statesman. Its sequel, The Laws, expounds the influential doctrine of Natural.
Introduction; Note on the Text; Note on the Translation; Bibliography; Table of Dates; THE REPUBLIC; THE LAWS; Appendix: Notes on the Roman Constitution; Explanatory Notes; Index of Names.
Includes bibliographical references (pages xxxvi-xli) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Political science -- Early works to 1800.; State, The -- Early works to 1800.; Rome -- Politics and government -- 265-30 B.C.; État -- Ouvrages avant 1800.; Rome -- Politique et gouvernement -- 265-30 av. J.-C.; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; POLITICAL SCIENCE -- Essays; Politics and government; Political science; State, The; Rome (Empire); 265-30 B.C; Early works; Didactisch proza (teksten)